Brazil and Latin America in the telereality from Davos to Belém: the journalistic coverage of the Brazilian newscasts - Becker, Beatriz; Teixeira, Juliana (Brazilian journalism research, 2009)
Television and news reports function as fundamental tools in order to amplify or restrict public interest. Journalistic discourses are strategic as mediators among the different powers and the civic society, and contribute to maintaining or transforming social practices, especially the narratives of the TV news. This work aims at identifying how television news programs build political dimensions, identities and Latin-American physical and symbolic territories, starting from an analysis covering two events that marked the international agenda in 2009: the World Economic Forum in Davos, and the World Social Forum in Belém, as treated by the most watched Brazilian television news programs.